A phenothiazine–rhodamine ratiometric fluorescent probe for Hg2+ based on FRET and ICT. Issue 29 (15th July 2015) - Zhao, Wenqi; Liu, Xingliang; Lv, Haitang; Fu, Hua; Yang, Yan; Huang, Ziping; Han, Aixia
Graphical abstract: Highlights: A novel probe1 is developed based on the phenothiazine–rhodamine platform for Hg 2+ ion detection. The probe is based on fluorescence resonance energy transfer (FRET) and internal charge transfer (ICT) mechanisms. The detection of Hg 2+ ion was not affected by the presence of other common ions. The probe produces a lower detection limit (1.8 ppb). Abstract: Rhodamine B and phenothiazine building blocks have been used to synthesize a novel ratiometric fluorescent probe1 for Hg 2+ . Based on fluorescence resonance energy transfer (FRET) and internal charge transfer (ICT) mechanisms, a low detection limit for Hg 2+ of 1.8 ppb has been achieved. The intensity ratio (F580 nm/F520 nm) of fluorescent probe1 increased on going from 0.1 to 1.0 equiv of Hg 2+ . In the FRET process, energy is transferred from the phenothiazine moiety to the rhodamine B moiety. Probe1 shows a selective response to Hg 2+ by color and fluorescence changes.